Solvent polarity‐dependent ESIPT behavior for 5‐(benzothiazole‐2‐yl)‐4‐hydroxyisophthalaldehyde fluorophore: A theoretical study. Issue 7 (3rd July 2022) - Guan, Yanlong; Tang, Zhe; Ju, Liping; Zhao, Jinfeng
Abstract: In view of the potential applications of 5‐(benzothiazole‐2‐yl)‐4‐hydroxyisophthalaldehyde (BHI) in the rapid identification of cyanide, the mechanism of excited‐state intramolecular proton transfer (ESIPT) of BHI has been studied in this work. By exploring the geometric parameters of hydrogen bonding in aprotic solvents with different polarities, infrared (IR) vibrational spectroscopy can confirm that hydrogen bonding is enhanced in the first excited state (S1 ). It is worth mentioning that the enhancement of hydrogen bonding in the S1 state by polar solvents is particularly important. In light‐induced excitation, by comparing the energy gaps of the leading molecular orbitals and the charge recombination around the proton acceptor and donor in aprotic solvents of different polarities, it is further predicted that polar solvents can promote the ESIPT process of BHI. In order to clarify the detailed ESIPT mechanism, we constructed the potential energy curves, searched for the transition state (TS) form, and determined the ESIPT mechanism for BHI fluorophore. Herein, we not only elucidated the excited‐state behavior of BHI, but also proposed a mechanism for regulating ESIPT by solvent polarity. Abstract : The enhancement of hydrogen bond of BHI fluorophore facilitates the ESIPT process. The charge redistribution is favorable for promoting the ESIPT reaction. The increasement of solvent polarity favors the ESIPT behavior of the BHI system.